Structure determination of gold clusters by trapped ion electron diffraction: Au14 –Au19 - - Lechtken, Anne; Neiß, Christian; Kappes, Manfred M.; Schooss, Detlef (Physical Chemistry Chemical Physics, 2009)
The structures of mass-selected gold cluster anions Au-Au have been reinvestigated using an improved low temperature trapped ion electron diffraction experiment. Structures were assigned by comparing experimental with simulated scattering functions using model structures obtained by density functional calculations. Flat three-dimensional structures are found for Au and Au, hollow cages for Au-Au and a tetrahedral structure is found for Au. For several clusters in this series, our assignments differ distinctly from previous assignments. © the Owner Societies 2009.